Acceptance of transvaginal sonography by postmenopausal women participating in the United Kingdom Collaborative Trial of Ovarian Cancer Screening. (11th December 2012) - Gentry‐Maharaj, A.; Sharma, A.; Burnell, M.; Ryan, A.; Amso, N. N.; Seif, M. W.; Turner, G.; Brunell, C.; Fletcher, G.; Rangar, R.; Fallowfield, L.; Campbell, S.; et al.
ABSTRACT: Objective: To assess pain and overall experience of transvaginal sonography (TVS) in asymptomatic postmenopausal women . Methods: In the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS), 50 639 postmenopausal women were randomized to undergo annual TVS at 13 trial centers in England, Wales and Northern Ireland. Together with the appointment letter for their annual scan, a random sample of 150 women per center was sent a detailed 48‐item postal questionnaire regarding the screening experience. It included a specific question about pain using a score of 0–5, where 5 was severe pain and 3 was discomfort. To assess factors that might affect a woman's reported pain experience, the pain score was regressed on age, hormone replacement therapy use, body mass index, a history of hysterectomy, prolonged scanning time, ovarian visualization, scan result, sonographer's visualization rates and opinion of the women regarding the sonographer who performed the scan . Results: Between 7 July and 9 September 2009, 1950 randomly chosen women (150 per regional center) were sent the questionnaire. Of the 800 (41.0%) who returned the questionnaire, 651 could be linked to their TVS appointment. One‐hundred and fifty‐two (23.3%) women reported pain/discomfort (score 3–5) during TVS and 473 (72.7%) reported no discomfort (score 0–2). Only 23 (3.5%) women reported experiencing moderate/severe pain. Increasing discomfort/pain was independently associated with a history of hysterectomy and participant's reporting of prolonged scan time. Women who experienced pain on TVS were less compliant (odds ratio = 0.87) with the following year's scan compared with those who did not experience pain . Conclusions: The majority of postmenopausal women found TVS acceptable. Pain influenced compliance and correlated with women's perception of increased scanning time and previous hysterectomy .Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.